MOLECULAR CHARACTERIZATION, BIOFILM FORMATION AND ANTIBIOGRAM ANALYSIS OF ENTEROTOXIGENIC BACILUS CEREUS FROM MILK AND MILK PRODUCTS IN PUDUCHERRY - S. Sathiesh; V. Bhanu Rekha; V. J. Ajay Kumar; J. Thanislass; R. Sivachandiran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present investigation was undertaken to study the occurrence of enterotoxigenic B. cereus from 200 samples including 100 raw milk, 50pasteurized milk and 50 ice cream samples sold in Puducherry. The results revealed that 68 samples (34 %) belonged to B. cereus group which included 36 from raw milk (36%), 9 from pasteurized milk (18%) and 23 from ice cream samples (46 %). On PCR analysis, 64 out of 68 isolates showed the presence of gyrB gene which differentiates B. cereus from B. cereus group isolates. Multiplex PCR revealed the presence of four enterotoxigenic genes hblA, nheA, cytK and entF Min 32.35 %, 77.94 %>, 54.41 % and 94.12% of the 64 isolates. On biofilm production assay, out of 64 enterotoxigenic B. cereus isolates, 60 (93.75 %) isolates showed the ability to form biofilm in which 13 (20.31 %) were strong, 21 (32.81 %) were moderate and26 (40.63 %) were weak biofilm producers. All the isolates were resistant to ampicillin and penicillin G and sensitive to ciprofloxacin, gentamicin, vancomycin, streptomycin and norfloxacin. The current study directs the need for proper hygienic measures during collection, production, processing and storage of milk to reduce the contamination level. It also indicates the need for surveillance and action to reduce the contamination of enterotoxigenic B. cereus in milk and milk products in Puducherry.